2015
DOI: 10.5152/eurjrheumatol.2015.0075
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of spondyloarthropathy in patients with psoriasis by using the ultrasonography and magnetic resonance image

Abstract: Objective: To assess the validity of ultrasound (US) in the early detection of arthritis and enthesitis, with assessment of the validity of magnetic resonance imaging (MRI) in the early detection of sacroiliitis and spondylitis in patients with psoriasis and to compare the findings of clinical examination and conventional radiography. Material and Methods:The study included 50 patients with psoriasis and 20 healthy controls. All patients and controls underwent US and power Doppler analyses for the joints of bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…In addition, our results were consistent with the previous results of FitzGerald and Gladma 18 that revealed that the presence of rheumatic complains especially LBP is a strong predictor of early axSpA changes in patients with PsA. Hamdy et al19 also reported that the presence of inflammatory back pain was the most important clinical feature associated with early signs of MRI sacroiliitis.…”
supporting
confidence: 93%
See 2 more Smart Citations
“…In addition, our results were consistent with the previous results of FitzGerald and Gladma 18 that revealed that the presence of rheumatic complains especially LBP is a strong predictor of early axSpA changes in patients with PsA. Hamdy et al19 also reported that the presence of inflammatory back pain was the most important clinical feature associated with early signs of MRI sacroiliitis.…”
supporting
confidence: 93%
“…Although there are several suggestive indicators and predictors for detecting early axSpA changes in patients with psoriasis and PsA regarding clinical and MRI findings, 6,18‐21 from our point of view this study proved that IL‐17A is the most accurate and the preferred method for detecting the early sub‐clinical axSpA changes in patients with nr‐axSpA (patients with inflammatory LBP with normal X‐ray findings) and asymptomatic psoriatic patients as it is a more precise and objective test than clinical data and has a low cost compared to MRI but with an equal prognostic value.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Therefore, it is necessary to rely on imaging rather than clinical examination in order to detect non-accessible sites of entheses. Indeed, numerous studies have shown that ultrasound (US) could detect a subclinical enthesitis in PsA patients [ 34 – 36 ].…”
Section: Evaluating Enthesitismentioning
confidence: 99%
“…The ultrasound images may detect early involvement of joints and tendons; moreover, some specific ultrasonographic patterns of PsA have been used in the differential diagnosis between PsA and rheumatoid arthritis. 8,9 Without regularity, she had used deflazacort, NSAID, and methotrexate with improvement of symptoms. Notwithstanding, the role of prevention and control of risk factors of severe forms of disease and associated comorbidities should be emphasized in this group of patients.…”
Section: Psoriatic Arthritismentioning
confidence: 99%